2016
DOI: 10.5370/jeet.2016.11.5.1337
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the Electrical Parameters of Degraded Solar Cells by Ultrasonic Treatment

Abstract: -In the lifetime of solar cells and under normal operating conditions, electrical parameters of solar cells are degrading continuously because solar cells are ageing during outdoor exposure, which could deteriorate their electrical characteristics. In this paper, to simulate and accelerate the effects of aging, solar cells are exposed to the different doses of gamma radiation, since gamma radiation and aging produces similar effects in semiconducting devices. The electrical parameters of degraded silicon solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Düşük dozda gözlenen azalma, azınlık yük taşıcılarının yaşam süreleri veya difüzyon uzunluğundaki azalma ile ilişkilendirilmektedir [9,22,23]. Radyasyon indüklü oluşan kusurlar yarıiletken malzemenin band aralığı içerisinde yeni tuzak enerji seviyeleri oluşturarak azınlık yük taşıyıcılarının ömürlerinin azalmasına neden olmaktadır [24]. Bu nedenle, azınlık yük taşıyıcılarının yaşam süreleri -indüklü kusurlara duyarlı olup, bu durum güneş hücrelerinin elektriksel özelliklerini olumsuz etkilemektedir [25].…”
Section: Bulgular (Results)unclassified
“…Düşük dozda gözlenen azalma, azınlık yük taşıcılarının yaşam süreleri veya difüzyon uzunluğundaki azalma ile ilişkilendirilmektedir [9,22,23]. Radyasyon indüklü oluşan kusurlar yarıiletken malzemenin band aralığı içerisinde yeni tuzak enerji seviyeleri oluşturarak azınlık yük taşıyıcılarının ömürlerinin azalmasına neden olmaktadır [24]. Bu nedenle, azınlık yük taşıyıcılarının yaşam süreleri -indüklü kusurlara duyarlı olup, bu durum güneş hücrelerinin elektriksel özelliklerini olumsuz etkilemektedir [25].…”
Section: Bulgular (Results)unclassified
“…It is revealed that V OC , FF and PCE decreases while increasing the temperature while J SC increases almost linearly in both cases. Increased temperature can cause reduction in the band gaps and can increase the collision between electron hole pairs and other atoms which leads to increase the recombination, so it will decrease the overall performance of the device [33][34][35]. It is also found that all the parameters provide better results in case of the device with hole transport layer.…”
Section: Impact Of Operating Temperature Variationmentioning
confidence: 99%
“…where τ is a minority carrier of lifetime. According to [24][25][26] minority carrier lifetime is highly degraded by the solar cell ageing during outdoor exposure. Thus, the electrical parameters of the solar cell are more likely to change with time.…”
Section: Dynamic Pv Modellingmentioning
confidence: 99%
“…The diffusion capacitance Cd is notable during forward‐bias of the p–n junction, and its value depends on the frequency and voltage according to [22]Cd=τq2kTI0expqVnormalankT,ωτ<<1 where τ is a minority carrier of lifetime. According to [24–26] minority carrier lifetime is highly degraded by the solar cell ageing during outdoor exposure. Thus, the electrical parameters of the solar cell are more likely to change with time.…”
Section: Dynamic Pv Modellingmentioning
confidence: 99%